2022
DOI: 10.1111/tpj.15674
|View full text |Cite
|
Sign up to set email alerts
|

Rerouting of the lignin biosynthetic pathway by inhibition of cytosolic shikimate recycling in transgenic hybrid aspen

Abstract: Lignin is a phenolic polymer deposited in the plant cell wall, and is mainly polymerized from three canonical monomers (monolignols), i.e. p-coumaryl, coniferyl and sinapyl alcohols. After polymerization, these alcohols form different lignin substructures. In dicotyledons, monolignols are biosynthesized from phenylalanine, an aromatic amino acid. Shikimate acts at two positions in the route to the lignin building blocks. It is part of the shikimate pathway that provides the precursor for the biosynthesis of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 93 publications
1
10
0
Order By: Relevance
“…This result indicated that the amount of ECH and its chemical composition influenced the thermal stability of the modified lignin samples. After graft modification by the epoxy group, the initial degradation temperature of the modified lignin was higher than that of unmodified lignin EL0, which could be due to the better thermal stability of EL0 side chains and their inhibitory effects on the thermal degradation of copolymers . The residue chars of EL0, EL10, EL20, and EL30 were 39.5, 37.2, 32.4, and 36.1%, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…This result indicated that the amount of ECH and its chemical composition influenced the thermal stability of the modified lignin samples. After graft modification by the epoxy group, the initial degradation temperature of the modified lignin was higher than that of unmodified lignin EL0, which could be due to the better thermal stability of EL0 side chains and their inhibitory effects on the thermal degradation of copolymers . The residue chars of EL0, EL10, EL20, and EL30 were 39.5, 37.2, 32.4, and 36.1%, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…(2022) P. alba × P. glandulosa miR393 suppression via STTM slightly ↑ n.d. n.d. n.d. Chu et al. (2021) P. tremula × Populus tremuloides HpSK overexpression WT ↑S/G, increased H units n.d. Hu et al. (2022) P. alba × P. grandidentata QsuB overexpression ↓33% ↑S/G n.d. WT Unda et al.…”
Section: Altering Lignin Amount and Composition Via Pathway Engineeringmentioning
confidence: 99%
“…Besides core genes of the lignin biosynthetic pathway, metabolic flux through the pathway can also be engineered via the depletion of essential co-factors. The expression of a bacterial SHIKIMATE KINASE ( SK ) gene in poplar results in a reduced shikimate pool in the cytoplasm, thereby hindering the HCT reaction for which shikimate is an essential substrate ( Hu et al., 2022 ). The resulting transgenic poplars have a lignin content comparable to that of WT plants, but an increased amount of H units, a reduction in ether-linked G and S units, and a biomass yield penalty ( Hu et al., 2022 ).…”
Section: Altering Lignin Amount and Composition Via Pathway Engineeringmentioning
confidence: 99%
See 2 more Smart Citations